2016
DOI: 10.1093/pubmed/fdw134
|View full text |Cite
|
Sign up to set email alerts
|

Clustering of health-related behaviors among early and mid-adolescents in Tuscany: results from a representative cross-sectional study

Abstract: BackgroundA huge amount of literature suggests that adolescents’ health-related behaviors tend to occur in clusters, and the understanding of such behavioral clustering may have direct implications for the effective tailoring of health-promotion interventions. Despite the usefulness of analyzing clustering, Italian data on this topic are scant. This study aimed to evaluate the clustering patterns of health-related behaviors.MethodsThe present study is based on data from the Health Behaviors in School-aged Chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 40 publications
2
19
1
1
Order By: Relevance
“…Most studies show smoking clusters with alcohol abuse in complex ways [10,21]. One study in Italy using HBSC data found 6 clusters ("smoking drinker", "nondrinking smoker", "quasi-healthy", "symptomatic", "violent" and "screen passion") [22]. Similarly, in our study alcohol and tobacco use both clustered in the same group ("Substance users"), comprising older adolescents.…”
Section: Cluster Patterns and Individual Factorssupporting
confidence: 71%
“…Most studies show smoking clusters with alcohol abuse in complex ways [10,21]. One study in Italy using HBSC data found 6 clusters ("smoking drinker", "nondrinking smoker", "quasi-healthy", "symptomatic", "violent" and "screen passion") [22]. Similarly, in our study alcohol and tobacco use both clustered in the same group ("Substance users"), comprising older adolescents.…”
Section: Cluster Patterns and Individual Factorssupporting
confidence: 71%
“…However, different from our results, they also identified the least time being sedentary. The literature remains inconsistent with some observational studies showing that clusters with high levels of PA are characterized by low levels of SB or screen time [ 26 28 ], whereas others reported a coexistence of high levels of both in the same cluster [ 5 , 26 ]. Dumuid et al [ 15 ] observed, among samples of children from twelve different countries, that the cluster of high screen time and high PA appears only for Brazilians, corroborating our results.…”
Section: Discussionmentioning
confidence: 99%
“…This clustering is reflected in the recent adoption of 24-h movement guidelines in Canada [ 20 ] and Australia [ 14 ], which recognize the importance of addressing physical activity, sedentary behavior/screen time, and sleep in conjunction. Alcohol use and smoking are also known to commonly co-occur [ 21 ], and the clustering of physical activity, diet, and sedentary behavior in adolescence is well established [ 22 ]. Evidence suggests this clustering differs by sex, with adolescent females comprising unhealthy clusters characterized by low physical activity [ 22 ], and females more likely than males to engage in multiple risk behaviors [ 23 ].…”
Section: Introductionmentioning
confidence: 99%